Fast peptide exchange on major histocompatibility complex class I molecules by acidic stabilization of a peptide‐empty intermediate. (17th November 2022) - Saikia, Ankur; Hadeler, Andries; Prasad, Pranathi; Zacharias, Martin; Springer, Sebastian
Abstract: The cell biology and biochemistry of peptide exchange on major histocompatibility complex class I (MHC‐I) proteins are of great interest in the study of immunodominance, which requires iterative optimization of peptide affinity, and cross‐presentation of pathogen and tumor antigens, in which endogenous peptides are exchanged for exogenous ones. Even though several methods exist to catalyze peptide exchange on recombinant MHC‐I proteins, the cellular conditions and mechanisms allowing for peptide exchange in vivo remain unclear. Here, we demonstrate that low pH, as present in endosomes, indeed triggers peptide exchange, and we dissect the individual steps of the exchange reaction. We find that low pH stabilizes the peptide‐empty forms of MHC‐I that occur as intermediates of the exchange reaction, and that is synergizes with dipeptides and with disulfide‐mediated stabilization of MHC‐I.